Hydrothermal syntheses of tungsten doped TiO2 and TiO2/WO3 composite using metal oxide precursors for charge storage applications - Pal, Bhupender; Vijayan, Bincy Lathakumary; Krishnan, Syam G.; Harilal, Midhun; Wan Jeffrey, Basirun; Lowe, Adrian E.; M. M., Yusoff; Rajan, Jose (Elsevier Ltd, 2018)
Synthesis of advanced functional materials through scalable processing routes using greener approaches is essential for process and product sustainability. In this article, syntheses of nanoparticles of titanium dioxide (TiO2), tungsten trioxide (WO3), WO3-doped titanium dioxide (W-TiO2) and TiO2/WO3 composite at hydrothermal conditions using corresponding metal oxide precursors are described. Electrochemical charge storage capabilities of the above materials are measured using cyclic voltammetry, charge-discharge cycling and electrochemical impedance spectroscopy in aqueous KOH electrolyte. The TiO2 and the WO3 nanoparticle showed a specific charge (Q) of ∼12 and ∼36 mA h g−1 at a current density of 2 A g−1 in 6 M KOH, respectively. The Q of TiO2 increased upon W doping up to 25 mA h g−1 for 5 wt% W-TiO2 and the WO3/TiO2 composite showed the highest storage capability (Q ∼40 mA h g−1). Changes in the charge storage capabilities of the doped and composite materials have been correlated to materials properties.